Accelerating Sulfur Redox Reactions by Topological Insulator Bi2Te3 for High‐Performance Li‐S Batteries - Song, Xueqin; Tian, Da; Qiu, Yue; Sun, Xun; Jiang, Bo; Zhao, Chenghao; Zhang, Yu; Fan, Lishuang; Zhang, Naiqing (Advanced functional materials, 2022)
Polysulfide shuttling and sluggish sulfur redox kinetics hinder the cyclability and rate capability of lithium‐sulfur (Li‐S) batteries. Accelerating sulfur redox reactions is considered a promising way toward the capture and utilization of soluble sulfur species. Herein, topological insulator (TI) Bi2Te3 is reported as an electrocatalyst for accelerated sulfur electrochemistry. The findings indicate that Bi2Te3 can effectively anchor soluble sulfur species and form seamless electron transport pathways with the adsorbed polysulfides. Both the sulfur reduction reactions and the reverse processes are found to be boosted by Bi2Te3. The incorporation of Bi2Te3 enables efficient operation of Li‐S batteries in terms of impressive rate capability of 857 mAh g−1 at 3 C and very low capacity decay of 0.033% per cycle over 1000 cycles. This work extends the application of TI to the field of Li‐S electrochemistry and may inspire further explorations. Topological insulator Bi2Te3 is reported as an electrocatalyst for accelerated sulfur electrochemistry. Bi2Te3 can not only effectively anchor soluble sulfur species but also form seamless electron transport pathways with the adsorbed polysulfides. Both the charge and discharge processes are significantly boosted by the incorporation of Bi2Te3. Consequently, high‐efficiency lithium‐sulfur batteries are obtained.